Mutations in a novel gene, NPHP3, cause adolescent nephronophthisis, tapeto-retinal degeneration and hepatic fibrosis - Olbrich, Heike; Fliegauf, Manfred; Hoefele, Julia; Kispert, Andreas; Otto, Edgar; Volz, Andreas; Wolf, Matthias T.; Sasmaz, Gürsel; Trauer, Ute; Reinhardt, Richard; Sudbrak, Ralf; Antignac, Corinne; et al. (Nature genetics, 2003)
Nephronophthisis (NPHP), a group of autosomal recessive cystic kidney disorders, is the most common genetic cause of progressive renal failure in children and young adults1. NPHP may be associated with Leber congenital amaurosis, tapeto-retinal degeneration, cerebellar ataxia, cone-shaped epiphyses, congenital oculomotor apraxia and hepatic fibrosis2,3,4,5,6. Loci associated with an infantile type of NPHP on 9q22-q31 (NPHP2), juvenile types of NPHP on chromosomes 2q12-q13 (NPHP1) and 1p36 (NPHP4) and an adolescent type of NPHP on 3q21-q22 (NPHP3) have been mapped7,8,9,10. NPHP1 and NPHP4 have been identified11,12,13, and interaction of the respective encoded proteins nephrocystin and nephrocystin-4 has been shown13. Here we report the identification of NPHP3, encoding a novel 1,330-amino acid protein that interacts with nephrocystin. We describe mutations in NPHP3 in families with isolated NPHP and in families with NPHP with associated hepatic fibrosis or tapeto-retinal degeneration. We show that the mouse ortholog Nphp3 is expressed in the node, kidney tubules, retina, respiratory epithelium, liver, biliary tract and neural tissues. In addition, we show that a homozygous missense mutation in Nphp3 is probably responsible for the polycystic kidney disease (pcy) mouse phenotype14. Interventional studies in the pcy mouse have shown beneficial effects by modification of protein intake and administration of methylprednisolone15,16,17, suggesting therapeutic strategies for treating individuals with NPHP3.
Gesehen am 22.06.2022